O uso de Anodontites trapesialis (Lamarck, 1819) como bioindicador e espécie modelo para estudos com microplástico - Silva, Maria Fernanda Rosa da (2026)
Microplastics (MPs) are now recognized as persistent components in all ecosystems, including rivers and lakes, especially in regions with inadequate waste and effluent management, as is the case in much of Brazil. In this scenario, understanding how different organisms interact with MPs is essential for both environmental monitoring and ecological risk assessment. Among the bioindicators used, bivalves stand out for their ease of collection, physiological sensitivity, filtering habit, and bioaccumulation capacity. The species Anodontites trapesialis, widely distributed in South American freshwater ecosystems, has proven to be a promising organism for studies with MPs due to its high filtration rate. This study integrates two complementary approaches, environmental monitoring and controlled experimentation, to evaluate the use of A. trapesialis as a bioindicator of MPs, with a special focus on fibers, the predominant type in freshwater environments. In both experiments, individuals were collected from the Pirajibu-mirim River (Sorocaba, SP) at different stations in April and December.One of the experiments analyzed the egestas (feces and pseudofeces) to assess contamination from the environment, while the second experiment involved a test with acute exposure to pristine polyester fibers. In general, A. trapesialis is already contaminated from the environment with a diversity of PMs and eliminates most of the particles in the first days of purification, taking at least 15 days to eliminate contamination from the environment. Regarding the fiber exposure experiment, the process follows the pattern of elimination of most fibers in the first 72 hours with no evidence of bioaccumulation after 21 days. The results also indicated that individuals ingest more 0.9 mm fibers than 4.0 mm fibers; however, size did not influence the total elimination time. In addition, 4.0 mm fibers exhibited changes after passing through the digestive tract, suggesting that internal structures, especially the crystalline stiletto, may act mechanically to modify the fibers, increasing the availability of smaller particles in the environment.